2009
DOI: 10.1007/978-3-642-01793-3_72
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Multiple Biometrics Grand Challenge

Abstract: The goal of the Multiple Biometrics Grand Challenge (MBGC) is to improve the performance of face and iris recognition technology from biometric samples acquired under unconstrained conditions. The MBGC is organized into three challenge problems. Each challenge problem relaxes the acquisition constraints in different directions. In the Portal Challenge Problem, the goal is to recognize people from nearinfrared (NIR) and high definition (HD) video as they walk through a portal. Iris recognition can be performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 12 publications
1
81
0
Order By: Relevance
“…Much progress has been made in developing systems to recognise faces in controlled, indoor environments. However, accurate recognition of human faces in unrestricted environments still remains a challenge [10]. This is due to significant intra-class variations caused by changes in illumination, head pose and orientation, occlusion, sensor quality and video resolution [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much progress has been made in developing systems to recognise faces in controlled, indoor environments. However, accurate recognition of human faces in unrestricted environments still remains a challenge [10]. This is due to significant intra-class variations caused by changes in illumination, head pose and orientation, occlusion, sensor quality and video resolution [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The expectation is that, the recognition accuracy can be improved by increasing the video resolution. Recent studies have shown that using high quality/resolution video result in better face recognition accuracy [1,14,10]. Law-enforcement, forensics, video surveillance and counter-terrorism are areas that can benefit from such biometric systems.…”
Section: Introductionmentioning
confidence: 99%
“…MASM is trained on a set of 500 images of 115 subjects manually annotated with these 68 landmarks and drawn from the National Institute of Standards and Tech nology (NIST) Multiple Biometric Grand Challenge -2008 (MBGC-2008) still face challenge database [22,23], which consists of 34,729 frontal images of 810 subjects. At the fitting stage, the Viola-Jones face detector [27] is used to detect faces in test images and initialize MASM.…”
Section: Resultsmentioning
confidence: 99%
“…Some the recent studies in this field are the Multiple Biometric Grand Challenge (MBGC 2009) [7] and the Face Recognition Vendor Test (FRVT 2006) [8], whose focus of research is shifting to recognizing faces taken under less constrained conditions. As a result of the evolution of this NIST challenges a new competition called GBU has been defined, which consists of three partitions called the Good, the Bad, and the Ugly.…”
Section: Variability In Unconstrained Environmentsmentioning
confidence: 99%
“…For the experiments in this paper, we use the segmented datasets provided by MBGC -Multiple Biometric Grand Challenge [7] compressed to 20KB with 120 pixels between the centers of the eyes. The faces were normalized following the ISO norm described in [3], from a size of 408 × 528 to size 168 × 192 pixels.…”
Section: Experimental Protocolmentioning
confidence: 99%